Internalisasi nilai moderasi beragama berbasis kearifan lokal pada siswa SMAN 13 Bone melalui pembelajaran PAI-BP - Inayati, Fajriah; Awaluddin, A. Fajar; HR, Sabriadi (Al-Liqo: Jurnal Pendidikan Islam, 2024)
This research aims to determine the internalization of the value of religious moderation based on local wisdom in UPT SMAN 13 Bone students through Islamic Religious Education and Character Learning. This research is qualitative research using a pedagogical approach and an Islamic Religious Education approach. Research data was obtained using interview, observation and documentation techniques. The research results found that the process of internalizing the value of religious moderation based on local wisdom in students was carried out through planning, implementation and evaluation in learning. Internalization through planning is included in the form of curriculum and lesson plans. The implementation is carried out through three stages, namely the transformation, transaction and value transinternalization stages. Meanwhile, the evaluation part is carried out through written tests and observations. The internalized values ​​are the value of tasamuh which is colored with Sipakatau, i'tidal colored with Sipakalebbi, and tahadhdhur colored with sipakatau, sipakalebbi, and sipakainge'.